EFFECTS OF TEMPERATURE ON APHID (HEMIPTERA: APHIDIDAE) ABUNDANCE IN FIELD CONDITIONS: A CASE STUDY OF ACYRTHOSIPHON PISUM AND THERIOAPHIS TRIFOLII ON ALFALFA - Jovičić, Ivana; Vujadinović, Mirjam; Vuković, Ana; Radonjić, Anđa; Petrović-Obradović , Olivera (Journal of Agricultural Sciences (Belgrade), 2022)
Populations of the most abundant alfalfa aphids, Acyrthosiphon pisum and Therioaphis trifolii, have periodic fluctuations, and many factors affect their dynamics. In the present study, we examined the impact of daily air temperatures on the abundance of two alfalfa aphids in field conditions. The numbers of these two aphids on alfalfa were documented at two locations in a representative alfalfa-growing area in Serbia, during a three-year-long field study. Based on the records of aphid abundance and daily air temperatures during the whole study, it was found that a correlation between the sum of optimal daily air temperatures for aphid development, the sum of maximum daily air temperatures and the number of recorded aphid peaks is significant and can therefore be considered for detection of suitable temperature conditions to increase aphid abundance. The study shows that the highest correlations were between a high density of A. pisum and the sum of optimal daily air temperatures for its development (Ck=0.569), and between a high density of T trifolii and the sum of maximum daily air temperatures (Ck=0.595). The length of time required for the growth of populations of the two alfalfa aphids differed: 30 days for A. pisum and 5 days for T. trifolii. Finding the association of temperature data to alfalfa aphid abundance enables a projection of their population behavior in changed future climate conditions. This study suggests increased population sizes of T. trifolii and decreased population sizes of A. pisum on alfalfa under the warmer conditions that are expected to prevail in the future.